2018
DOI: 10.2147/ott.s160831
|View full text |Cite
|
Sign up to set email alerts
|

MFAP2 promotes epithelial–mesenchymal transition in gastric cancer cells by activating TGF-β/SMAD2/3 signaling pathway

Abstract: IntroductionMicrofibril-associated protein 2 (MFAP2) is an extracellular matrix protein that interacts with fibrillin to modulate the function of microfibrils. MFAP2 has been reported to play a significant role in obesity, diabetes, and osteopenia, and has been shown to be upregulated in head and neck squamous cell carcinoma. However, the molecular function and prognostic value of MFAP2 have never been reported in gastric cancer (GC) or any other tumors.MethodsThe current study investigated the expression patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 50 publications
5
50
0
Order By: Relevance
“…3c, GC cell lines expressed more MFAP2 than GES-1. We also found that a previous study had verified that MFAP2 was upregulated in GC among 168 paired samples by immunohistochemistry 24 . These findings demonstrated that MFAP2 was upregulated in GC, implying the importance of them in GC pathogenesis.…”
Section: Mfap2 Is Upregulated In Gc Tissues and Cell Linessupporting
confidence: 79%
“…3c, GC cell lines expressed more MFAP2 than GES-1. We also found that a previous study had verified that MFAP2 was upregulated in GC among 168 paired samples by immunohistochemistry 24 . These findings demonstrated that MFAP2 was upregulated in GC, implying the importance of them in GC pathogenesis.…”
Section: Mfap2 Is Upregulated In Gc Tissues and Cell Linessupporting
confidence: 79%
“…MFAP2 is a component of microfibrils. 28 An in vivo assay shows that MFAP2 regulates hemostasis and thrombosis. 29 Few studies were conducted to investigate MFAP2 function in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MFAP2 has been shown to be markedly elevated in head and neck squamous cell carcinoma, particularly in lymph node metastasis (34). Recently, Wang et al (35) demonstrated that MFAP2 can promote epithelial-mesenchymal transition via activating the TGF-β/SMAD2/3 signaling pathway in GC cells. Consistent with previous findings, our results suggested that MFAP2 may play a crucial role in progression of GC and that it may act as an oncogene.…”
Section: Discussionmentioning
confidence: 99%